THE REGULATION OF PHYSICAL ACTIVITY IN THE PROCESS OF PHYSICAL EDUCATION OF STUDENTS WITH VISUAL IMPAIRMENT (Education in the 21st Century, 2023)
This article reveals the basic factors, signs and indicators of tiredness to be obligatoryconsidered in the process of organizing and conducting physical activities with students withdifferent types of visual impairment. As the different forms and degrees of visual impairment,psychophysical peculiarities of development, lack of development of motor skills and orientationsin space of those students determine the importance and necessity of using protective means andmobilizing stand-by resources at gym classes.It has been established, that the deep and partial visual impairment significantly impede themotor possibilities of students, their orientation in macro and micro-spaces, understanding theteaching material of physical education program and participating in the physical and sportactivities. Therefore, in order to prevent injuries and further visual impairments in students duringphysical activities in school, university and gyms, we have to take into account the gender, formand degree of visual impairment, the availability of concomitant diseases, secondarydevelopmental deviations, the level of physical preparedness of students and many other factors.This will serve as the basis for health strengthening in students with different types of visualimpairment. The abovementioned points define the relevant, theoretical and practical significanceof the present research theme